REVISING THE CONCEPTUALIZATION OF AGING IN CONSUMER BEHAVIOR. (11th November 2018) - Zniva, R; Weber, D
Abstract: The aim of the study at hand is to elaborate a status quo of measuring age in consumer behavior research and to identify new research avenues by introducing approaches from gerontology and demography. The study is based on a review of 145 papers on the behavior of consumers at advanced age published from 1980 to 2017 in 35 peer-reviewed journals. Following a rigorous search and selection process, studies analyzing quantitative data and published in journals ranked by Hartzing (2018) were selected. Independent variables, moderator, and mediator variables representing the age status of respondents were identified and categorized into five broad categories (chronological age, biological age, psychological age, social age and multi-theoretical approaches). Results of the review show that research on older consumers′ behavior is still dominated by chronological age. Only around 25% of the studies follow a more holistic perspective using non-chronological age measures. Furthermore, the use of non-chronological age is strongly limited to a variety of self-reported measures and can be hardly compared, due to well-known differences in self-reports. To integrate the parsimony and understanding of chronological age with the complexity of multidimensional aging and to improve comparison between non-chronological measures, we introduce the characteristic age approach from demography to consumer behavior research. We show by analyzing longitudinal and cross-sectional data, that the characteristic age approach increases comparability and understanding of different age processes and allows the usage of objective non-chronological age measures (e.g. grip strength) for theory building in consumer behavior research.